Routine Gynaecological Operations Without Blood Transfusion (Journal of Dhaka Medical College, 2020)
Objective : To establish the fact that most of the routine gynaecological operations need no blood transfusion.Method : This was a prospective observational study conducted in Dhaka Medical College Hospital from 15th January, 2011 to 14th April, 2011. Subjects were gynaecological patients admitted for routine operation. Main outcome variable was comparison of postoperative events between patients who received blood transfusion and who did not.Results : 40 gynaecological patients were operated without blood transfusion (Group I ) and 40 patients were taken who were operated with blood transfusion (GroupII ). Among the patients 35% in Group I and 42.5 % patients in Group II had some minor complications (hypotension, fever, wound infection and others) in postoperative period . The p value of of these postoperative complications in Group I is 0.020 and in Group II is 0.047 and r = 0.75 . The difference of pvalue is significant. No patient of any group sufferred from any major comcplication.Conclusion : There was no advantage of transfusing blood in routine gynaecological operation, rather more patients with blood transfusion had some minor postoperative complications.J Dhaka Medical College, Vol. 27, No.2, October, 2018, Page 123-126